Including self-care curricula to respond to PSTs' exposure to secondary trauma - Heather Bailie Schock; Yvonne Franco; Madelon McCall (Emerald Publishing, 2024)
Purpose - Most teacher preparation programs (TPP) provide little instruction on mitigating the stress-related consequences of teaching (Miller and Flint-Stipp, 2019). This study aims to provide empirical support for including a self-care unit in teacher preparation curricula to address the secondary trauma and stressors inherent to the teaching profession (Essential 2; NAPDS, 2021; Sutcher et al., 2019). Design/methodology/approach - This investigation occurred in an elementary TPP at a private southeastern US university and spanned two years, utilizing a mixed methods approach. Findings - Findings suggest that after experiencing a 5-week self-care unit, preservice teachers exhibited a statistically significant increase in well-being and a newfound recognition of the need to prioritize self-care for effective teaching, suggesting its potential effectiveness in reducing burnout and attrition. Research limitations/implications - While this study provided valuable insights into the implementation and impact of a self-care unit within the context of elementary education majors at a mid-sized private university in the USA, it is essential to acknowledge its limitations. One notable limitation is the relatively homogenous sample, primarily consisting of White female participants. Practical implications - The implications of this study are critical for teacher education policy and practice, advocating for including self-care curricula to enhance teacher well-being and, by extension, prepare teachers with a skillset to support their career trajectory (Essential 3; NAPDS, 2021). Originality/value - This recommendation underscores the collaborative efforts between TPPs and partnership schools to implement such initiatives effectively, representing a pivotal step toward better-preparing teachers to manage the demands of their profession while prioritizing their mental health (Essentials 4 & 5; NAPDS, 2021).